APPROPRIATE MODELS FOR MEASURING CREATIVE ACCOUNTING PRACTICES AND ITS IMPACT ON TAX RETURNS: APPLIED STUDY IN IRAQI GENERAL TAX AUTHORITY - Ban Abdul-Kadhm Abdulaali (Scholar Express Journals, 2025)
The research purposes to classify the degree to which some businesses repetition creative accounting (CA) processes, and the level to first outlining the nature of CA processes, their indications, their justifications, their methods of practice, and their ramifications, and then demonstrating the connection between CA practices and tax returns, they demonstrate their awareness of the hazards that arise from this. The Iraqi General Tax Authority served as the research sample for the 2015–2024 timeframe in order to examine the connection between tax returns and innovative accounting techniques. The research reached a number of conclusions, the most important of which was that CA practices have an impact on financial statements. This is because CA is a novel practice in which accountants use their understanding of accounting laws and regulations to process or manipulate numbers recorded in economic units' accounts in order to achieve particular goals. Tax returns are negatively impacted by the income statement's increasing or decreasing effects on expenses, revenues, total profit, and net profit. To hide defects and performance problems in order to achieve the intended results.
Keywords: Laws and regulations; CA practices